Using Public Engagement to Inform the Future of Health Care in Maine: Talking About “Tough Choices” - Beard, Ronald; Tanski, Tish (Maine Policy Review, 2005)
The biennial state health plan mandated by Maine’s innovative Dirigo Health Reform Act guides how the state makes decisions about using its health care resources. Public engagement in the development of this plan was made an explicit goal. Ron Beard and Tish Tanski discuss how nearly 400 Maine citizens were involved in a virtual town meeting in May 2005 that provided input on the state’s health plan. The collective voice of citizens involved in this forum has proven to be an important input in the ongoing efforts of policymakers to devise a responsive health care system.
Keywords: Maine; healthcare policy; Maine state health plan